RANCANG BANGUN SISTEM INFORMASI LAYANAN KEUANGAN TANPA KANTOR DALAM RANGKA KEUANGAN INKLUSIF - Usanto Usanto (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
Lakupandai (Officeless Financial Services in the Framework of Financial Inclusion) is a financial inclusion and financial literacy program promoted by the government so that more people can be accessed by financial services. Bank XYZ as one of the private banks in Indonesia plays a role in the success of this government program. The current system is still manual, so an information system is needed to accommodate these services. Based on these problems, the purpose of this study is to create a web-based cover-up information system. The research method used is to use the PIECES method (Performance, Information / Data, Economic, Control / Security, Efficiency, and Service) with the data analysis tools used are the uses case and activity diagrams. With the java programming language and postgres as a database. This research resulted in a design of an officeless financial service information system in the framework of financial inclusion which functions to accommodate banking services to make them better, more effective and more efficient